SLC12A ion transporter mutations in sporadic and familial human congenital hydrocephalus*. Issue 9 (8th August 2019) - Jin, Sheng Chih; Furey, Charuta G.; Zeng, Xue; Allocco, August; Nelson‐Williams, Carol; Dong, Weilai; Karimy, Jason K.; Wang, Kevin; Ma, Shaojie; Delpire, Eric; Kahle, Kristopher T.
Abstract: Background: Congenital hydrocephalus (CH) is a highly morbid disease that features enlarged brain ventricles and impaired cerebrospinal fluid homeostasis. Although early linkage or targeted sequencing studies in large multigenerational families have localized several genes for CH, the etiology of most CH cases remains unclear. Recent advances in whole exome sequencing (WES) have identified five new bona fide CH genes, implicating impaired regulation of neural stem cell fate in CH pathogenesis. Nonetheless, in the majority of CH cases, the pathological etiology remains unknown, suggesting more genes await discovery. Methods: WES of family members of a sporadic and familial form of severe L1CAM mutation‐negative CH associated with aqueductal stenosis was performed. Rare genetic variants were analyzed, prioritized, and validated. De novo copy number variants (CNVs) were identified using the XHMM algorithm and validated using qPCR. Xenopus oocyte experiments were performed to access mutation impact on protein function and expression. Results: A novel inherited protein‐damaging mutation (p.Pro605Leu) in SLC12A6, encoding the K + ‐Cl − cotransporter KCC3, was identified in both affected members of multiplex kindred CHYD110. p.Pro605 is conserved in KCC3 orthologs and among all human KCC paralogs. The p.Pro605Leu mutation maps to the ion‐transporting domain, and significantly reduces KCC3‐dependent K + transport. A novel de novo CNV (deletion) was identified in SLC12A7, encoding the KCC3 paralog and binding partner KCC4, in another family (CHYD130) with sporadic CH. Conclusion: These findings identify two novel, related genes associated with CH, and implicate genetically encoded impairments in ion transport for the first time in CH pathogenesis. Abstract : In this report, we have detailed the discovery of a novel damaging mutation in SLC12A6, encoding the KCC3 Cl ‐ cotransporter, in a novel familial syndrome of congenital hydrocephalus (CH). Furthermore, we discovered and validated a de novo copy number variation (deletion) in SLC12A7 ( KCC4 ) in a case with severe sporadic CH with aqueductal stenosis.